Preparation method and application of porous carbon material rich in micro-nano through holes and gas-phase silicon-carbon composite material

By using porous carbon material rich in micro-nano through-holes as the buffer structure for silicon expansion in lithium-ion batteries, and forming silicon-carbon composite materials by vapor deposition of nano-silicon particles, the problems of high expansion rate, poor conductivity and repeated growth of SEI films in lithium-ion batteries are solved, and better cycling performance and electrical conductivity are achieved.

CN119858909AActive Publication Date: 2025-04-22CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510345353.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The application of silicon-based materials in lithium-ion batteries is limited by problems such as high expansion rate, poor conductivity and repeated growth of SEI films, resulting in poor circulation performance.

Method used

A porous carbon material rich in micro-nano through-holes is used as the buffer structure for silicon expansion, and a porous carbon skeleton is prepared by isostatic pressure and vacuum sintering processes, and nanosilicon particles are deposited by vapor phase to form a silicon-carbon composite material to improve battery performance.

Benefits of technology

It effectively inhibits the powdering of silicon particles and the repeated growth of SEI film, improves the circulation performance and conductivity of lithium-ion batteries, and enhances the market competitiveness of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858909A_ABST
    Figure CN119858909A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a porous carbon material rich in micro-nano through holes and a gas-phase silicon-carbon composite material. The preparation method comprises the following steps: uniformly mixing a foaming agent and a carbon source, performing isostatic pressing treatment, and crushing an obtained isostatic pressing block to obtain crushed coarse particles; and then carrying out vacuum sintering treatment on the crushed coarse particles under the protection of inert gas to obtain original particles, and finally crushing the original particles to obtain the porous carbon material rich in micro-nano through holes. The prepared porous carbon skeleton rich in micro-nano through holes has rich micro-nano pores, and the pores are mostly of non-closed through hole structures, so that the pores are uniformly filled with vapor deposition nano silicon particles to form a composite structure with uniformly combined silicon and carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon material preparation and lithium ion battery, and in particular relates to a preparation method and application of a porous carbon material rich in micro-nano through pores and a gas phase silicon-carbon composite material. Background Art

[0002] After more than a decade of development, lithium-ion batteries have reached a bottleneck in improving their energy density. The main problem is that the lithium storage capacity of commercialized positive and negative electrode materials has basically reached the theoretical limit. Among them, the capacity of graphite carbon negative electrode materials has reached 360mAh / g, close to the theoretical value of 372mAh / g, and there is very little room for improvement. In order to achieve higher energy density, silicon-based materials with a theoretical gram capacity of up to 4200mAh / g have attracted widespread attention. Compared with graphite materials, the theoretical energy density of silicon-based materials is more than 10 times that of graphite materials, and is considered to be one of the most promising materials for high-specific-capacity negative electrode materials for lithium-ion batteries.

[0003] The main problem with the application of silicon negative electrode materials is that they expand greatly, with an expansion rate of up to 300%. The large expansion rate will eventually lead to the pulverization of active materials and the destruction of the SEI film on the surface during the application process, making the cycle performance worse; at the same time, due to the semiconductor properties of silicon, its conductivity is also poor, which is reflected in poor rate performance. Therefore, for the actual application of lithium-ion batteries, silicon negative electrode materials still face huge challenges. Summary of the invention

[0004] In order to overcome the problems in the prior art, the present invention provides a preparation method, application and gas-phase silicon-carbon composite material of a porous carbon material rich in micro-nano through pores. The porous carbon skeleton has abundant micro-nano pores, and most of the pores are non-closed through-hole structures, which is conducive to uniform filling of vapor-deposited nano-silicon particles into the pores to form a composite structure in which silicon and carbon are uniformly combined. The porous carbon material provides a buffer structure for silicon expansion, solving the problems of particle pulverization of silicon materials and repeated growth of surface SEI film.

[0005] In order to solve the above technical problems, the technical solutions proposed by the present invention are as follows: The invention provides a method for preparing a porous carbon material rich in micro-nano through pores, comprising the following steps.

[0006] S1. Mix the foaming agent and the carbon source uniformly and perform isostatic pressing to obtain an isostatic pressed block; the isostatic pressing pressure is 50-300 MPa and the processing time is 60-120 min.

[0007] S2, crushing the isostatically pressed blocks obtained in step S1 to obtain crushed coarse particles.

[0008] S3. The crushed coarse particles in step S2 are subjected to vacuum sintering treatment under the protection of an inert gas to obtain primary particles; the sintering temperature of the vacuum sintering is 600-900° C., the vacuum degree is maintained at -(1.0±0.5) Kpa, and the temperature is kept for 60-120 minutes.

[0009] S4, crushing the original particles in step S3 to obtain a porous carbon material rich in micro-nano through pores.

[0010] In the present invention, the sintered pore-forming carbon source powder is tightly combined to form a dense structure through an isostatic pressing process to prevent naturally formed large pores inside; at the same time, a small amount of foaming agent is added to perform vacuum sintering foaming pore-forming. During the vacuum sintering process, the foaming agent is first heated to form a gas volatilization to form a large number of pores. Further, under vacuum conditions, the high vapor pressure gas inside the sintered material can effectively escape to the outside, so that the internal pores can be opened, that is, a porous structure carbon with micro-nano through pores is formed after sintering. As the proportion of the foaming agent increases, the pore size of the material will increase.

[0011] As an optional embodiment, in the preparation method provided by the present invention, the foaming agent is selected from one or more of sodium bicarbonate, sodium carbonate, azodicarbonamide or carbon black; and the particle size D50 of the foaming agent is 1-10 μm.

[0012] The particle size D50 of the foaming agent is 1~10μm. In principle, the smaller the particle size, the more conducive it is to dispersion with the carbon source. However, the smaller the particles, the more difficult it is to process. Therefore, the particle size is limited to within 10 microns, which is conducive to dispersion and easy to process.

[0013] In the present invention, the volatilized gas of the foaming agent during the high-temperature sintering process can form a large number of internal pores, and due to the vacuum condition, the internal gas can escape to the outside under the high pressure difference, which is conducive to forming a porous structure with through holes.

[0014] As an optional embodiment, in the preparation method provided by the present invention, the carbon source is selected from one or more of asphalt, resin or organic polymer, and the particle size D50 of the carbon source is 1-30 μm.

[0015] As an optional embodiment, in the preparation method provided by the present invention, in step S1, the mass ratio of the foaming agent to the carbon source is (0.1~0.5):100.

[0016] In the present invention, controlling the mass ratio of the foaming agent to the carbon source within the above range is beneficial to forming the most excellent pores.

[0017] As an optional embodiment, in the preparation method provided by the present invention, in step S2, the size of the crushed coarse particles is 3-10 mm.

[0018] As an optional implementation, in the preparation method provided by the present invention, in step S3, the heating rate during vacuum sintering is 0.5-5°C / min.

[0019] As an optional embodiment, in the preparation method provided by the present invention, the pore size of the prepared porous carbon material rich in micro-nano pores is 0.5-10.0 nm; the pore volume accounts for 60-90%.

[0020] Based on the same technical concept, the present invention also provides the application of the porous carbon material rich in micro-nano through pores prepared by the above-mentioned preparation method in silicon-carbon composite materials or in lithium-ion batteries.

[0021] Based on the same technical concept, the present invention also provides a gas-phase silicon-carbon composite material, which is obtained by subjecting the porous carbon material rich in micro-nano through pores prepared above to silane chemical vapor deposition.

[0022] In the present invention, nano silicon is filled into porous carbon with rich micro-nano through-hole structure by vapor deposition. The porous carbon material rich in micro-nano through-holes provides a high-quality substrate for gas phase silicon and an elastic carrier for silicon particles, which inhibits the huge volume expansion of silicon during the charging and discharging process. At the same time, the majority of nano pores effectively protect silicon particles from direct contact reaction with electrolytes, reducing the occurrence of side reactions on the surface of silicon particles. Ultimately, the gas phase silicon-carbon composite material based on the porous structure has excellent performance.

[0023] As an optional embodiment, in the gas-phase silicon-carbon composite material provided by the present invention, the temperature of the silane chemical vapor deposition is (600±100)°C, and the flow ratio of the introduced silane gas to the protective gas is (0.5~1):10.

[0024] As an optional implementation, in the vapor phase silicon-carbon composite material provided by the present invention, the mass percentage of vapor phase deposited silicon (nano silicon) accounts for 40% to 60% of the total mass.

[0025] Furthermore, the preferred mass percentage is 45%.

[0026] As an optional embodiment, in the gas phase silicon-carbon composite material provided by the present invention, the gas phase deposition equipment is selected from one of an atmosphere rotary kiln or a fluidized bed deposition equipment.

[0027] As an optional embodiment, in the gas-phase silicon-carbon composite material provided by the present invention, the silane gas is selected from one or more of monosilane, disilane, trisilane, butadisilane, monochlorosilane or dichlorosilane.

[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) The porous carbon rich in micro-nano through-holes in the present invention has a rich micro-nano pore structure, which can provide sufficient carriers for gas-phase nano-silicon particles. The micro-nano pores are through-holes connected to the outside, which is conducive to the gas-phase deposited silicon particles filling into the pores, avoiding the silicon particles only being deposited on the surface and causing uneven deposition.

[0029] (2) The preparation method of the porous carbon material rich in micro-nano through-pore structure provided by the present invention mainly includes an isostatic pressing process and a vacuum sintering process, wherein the isostatic pressing process allows the carbon source powder to be tightly combined to form a dense structure before sintering and pore formation, thereby preventing the existence of naturally formed large pores inside; at the same time, a small amount of foaming agent is added for vacuum sintering and foaming to form pores. During the vacuum sintering process, the foaming agent is first heated to form a gas that volatilizes to form a large number of pores. Further, under vacuum conditions, the high vapor pressure gas inside the sintered material can effectively escape to the outside, so that the internal pores can be opened up, that is, a porous structure carbon with micro-nano through-pores is formed after sintering; at the same time, a small amount of foaming agent has very little residue after sintering, and no further special treatment is required, thereby reducing the cost of waste treatment.

[0030] (3) The silicon-carbon material prepared by using the porous carbon material of the present invention can solve the problem of particle pulverization of silicon material and repeated growth of SEI film on the surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 This is an electron microscope image of the porous carbon raw material rich in micro-nano through-pore structure prepared in Example 1 of the present invention; Figure 2 This is an electron microscope image of the silicon-carbon composite material prepared in Example 1 of the present invention; Figure 3 is a SEM photograph of a cross section of the gas phase silicon-carbon composite material particles prepared in Example 1 of the present invention; Figure 4 is a C element distribution diagram of a cross section of a gas phase silicon-carbon composite material particle prepared in Example 1 of the present invention; Figure 5 This is a diagram showing the Si element distribution in the cross section of the gas phase silicon-carbon composite material particles prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0034] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0036] Example 1 A method for preparing a gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure comprises the following steps: (1) Raw material mixing: Take a certain amount of sodium bicarbonate powder (D50≈5μm) and asphalt powder (asphalt PE250, coking value of about 48%, D50≈10μm) for physical mixing; the mass ratio of sodium bicarbonate powder to asphalt powder is 0.2:100; use a high-speed dispersing device (model VCH-5L), under nitrogen protection, the dispersion rate is 500rpm for 20min, and the dispersion rate is 1000rpm for another 30min; at the same time, the circulating cooling water is turned on throughout the process; after the raw materials are mixed, they are sealed and stored in PE bags.

[0037] (2) Isostatic pressing: The powder from step (1) is filled into a silicone soft mold, which is then vacuum-sealed with a PE bag. The sealed loading mold is placed in an isostatic pressing chamber (ultra-high pressure equipment model 600MPa-5L). The isostatic pressing parameters require a pressure of 200MPa and a holding time of 90min. After the pressing is completed, the PE bag is torn off and the block in the mold is taken out to obtain an isostatic pressed block.

[0038] (3) Crushing: The isostatically pressed block material of step (2) is crushed by a small jaw crusher (model PE100-125) for multiple crushing until the particle size is controlled to be less than 10 mm.

[0039] (4) Vacuum sintering: The crushed material in step (3) is vacuum sintered in a vacuum sintering furnace (model HF-RS-A). The temperature control of the vacuum sintering furnace is carried out according to the following requirements: vacuum is first evacuated before heating, and the temperature is started after the vacuum degree reaches -1.0 kPa; then the temperature is raised from room temperature to 700°C, the heating rate is 1°C / min, and the temperature is kept for 120 minutes; after the end, the heating is turned off and the material is naturally cooled to room temperature. The vacuum degree of the entire sintering process needs to be maintained in the range of -(1.0±0.5) kPa. If the vacuum degree is lower than this range, the vacuum pump is started to evacuate. In this way, a porous carbon raw material with a micro-nano through-hole structure is obtained.

[0040] (5) Crushing: The raw material of step (4) was further crushed in a jet mill (model QLM-1.5) to obtain a porous carbon raw powder rich in micro-nano pore structure, named PC1.

[0041] (6) Vapor deposition: The original powder of step (5) was subjected to vapor phase silicon deposition in a fluidized bed device (model FB-100), 5 kg of the original powder was added, and high-purity argon was first passed for 30 minutes at a flow rate of 10 L / min; then the temperature was raised from room temperature to 560°C at a heating rate of 5°C / min, and after being kept at 560°C for 30 minutes, monosilane gas was passed at a flow rate of 0.1 L / min, and the high-purity argon flow rate was kept constant at 10 L / min. After the deposition reached 8 hours, the methane gas was stopped, and the high-purity argon flow rate was kept constant at 10 L / min. The heating was turned off and the mixture was naturally cooled to room temperature. A vapor phase silicon-carbon composite material based on porous carbon rich in micro-nano through-hole structure was obtained, which was named SPC1.

[0042] Example 2 A method for preparing a gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure, which differs from Example 1 in that: The sodium bicarbonate powder in step (1) is replaced with sodium carbonate powder (sodium carbonate, D50≈5μm), and the mass ratio of sodium carbonate powder to asphalt powder is 0.1:100; the medium static pressure parameters in step (2) require a pressure of 100MPa and a holding time of 120min; in step (4), the temperature is increased from room temperature to 900°C at a heating rate of 3°C / min and the temperature is kept for 100min. The other steps are consistent with Example 1. The porous carbon original powder rich in micro-nano through-pore structure is named PC2, and the gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure is obtained, which is named SPC2.

[0043] Example 3 A method for preparing a gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure, which differs from Example 1 in that: The sodium bicarbonate powder in step (1) is replaced with carbon black powder (acetylene black, D50≈1 μm), and the mass ratio of acetylene black powder to asphalt powder is 0.3:100; in step (4), the temperature is raised from room temperature to 600°C, the heating rate is 1°C / min, and the temperature is kept for 100 minutes. The other steps are consistent with Example 1. The porous carbon original powder rich in micro-nano through-pore structure is obtained and named PC3, and the gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure is obtained and named SPC3.

[0044] Example 4 A method for preparing a gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure, which differs from Example 1 in that: The asphalt PE250 powder in step (1) is replaced with phenolic resin 2123 powder (phenolic resin 2123, coking value 48%, D50≈13μm), and the mass ratio of sodium bicarbonate powder to phenolic resin powder is 0.4:100; the medium static pressure parameters in step (2) require a pressure of 300MPa and a holding time of 80min; in step (4), the temperature is raised from room temperature to 800°C, the heating rate is 3°C / min, and the temperature is kept for 100min. The other steps are consistent with Example 1. The porous carbon original powder rich in micro-nano through-pore structure is named PC4, and the gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure is obtained, which is named SPC4.

[0045] Example 5 A method for preparing a gas phase silicon-carbon composite material based on porous carbon rich in micro-nano through-pore structure, which differs from Example 1 in that: The asphalt PE250 powder in step (1) was replaced with nylon powder (nylon 66, coking value 48%, D50≈10 μm), and the mass ratio of sodium bicarbonate powder to nylon powder was 0.5:100; the other steps were consistent with Example 1. The porous carbon raw powder rich in micro-nano through-pore structure was obtained and named PC5, and the gas phase silicon-carbon composite material based on the porous carbon rich in micro-nano through-pore structure was obtained and named SPC5.

[0046] Comparative Example 1 A method for preparing a gas phase silicon-carbon composite material based on a porous carbon material is different from Example 1 in that: The amount of foaming agent added in step (1) is 0, and the other steps are consistent with Example 1. The obtained porous carbon raw powder is named PC6, and the obtained gas phase silicon-carbon composite material based on porous carbon is named SPC6.

[0047] Comparative Example 2 A method for preparing a gas phase silicon-carbon composite material based on a porous carbon material is different from Example 1 in that: The vacuum sintering in step (4) was replaced by atmospheric pressure sintering. The maximum sintering temperature and temperature rise program of atmospheric pressure sintering were consistent with those in Example 1. The vacuum environment was changed to nitrogen as protective gas throughout the process, with a ventilation rate of 1.0 L / min. The other steps were consistent with those in Example 1. The obtained porous carbon raw powder was named PC7, and the obtained gas phase silicon-carbon composite material based on porous carbon was named SPC7.

[0048] Comparative Example 3 A method for preparing a gas phase silicon-carbon composite material based on a porous carbon material is different from Example 1 in that: In step (1), a higher amount of sodium bicarbonate is added, and the added amount is a mass ratio of sodium bicarbonate powder to asphalt powder of 1.0:100; the other parameters remain unchanged. Other parameters and steps are consistent with Example 1. The obtained porous carbon raw powder is named PC8, and the obtained gas phase silicon-carbon composite material based on porous carbon is named SPC8.

[0049] Comparative Example 4 A method for preparing a gas phase silicon-carbon composite material based on a porous carbon material is different from Example 1 in that: In step (2), isostatic pressing is not performed, and step (4) is directly performed for sintering after mixing in step (1), and the other steps are consistent with Example 1. The obtained porous carbon raw powder is named PC9, and the obtained gas phase silicon-carbon composite material based on porous carbon is named SPC9.

[0050] 1. Preparation of button electrode Electrode preparation: The gas-phase silicon-carbon composite materials prepared in the above embodiments and comparative examples are respectively mixed with conductive agent SP, binder LA133 and deionized water in a certain proportion to form a uniform slurry, wherein the mass ratio of silicon-carbon negative electrode material: conductive agent SP: binder LA133 is 60:20:20; the slurrying equipment uses a vacuum degassing machine with a rotation speed of 2000 rpm and a time of 10 min.

[0051] The prepared slurry is evenly coated on the copper foil, and then placed in a 100°C forced air drying oven for drying; the baked electrode pieces are cut and pressed into circular electrodes of a certain size, accurately weighed (accurate to 0.0001g), placed in a vacuum drying oven, and baked at 120°C for 8h under vacuum conditions to obtain button electrodes.

[0052] The button cell assembled with the SPC1 material is recorded as SC1 button cell, and by analogy, seven types of button cells SPC1 to SPC9 are obtained.

[0053] 2. Performance Testing 1. Performance testing of gas phase silicon-carbon composite materials based on porous carbon rich in micro-nano through-pore structure.

[0054] The pore volume and pore size of the porous carbon raw materials rich in micro-nano through-pore structure prepared in the above-mentioned embodiments and comparative examples were tested, and the results are shown in Table 1.

[0055] Table 1: Pore structure of porous carbon

[0056] The porous carbon materials prepared in Comparative Examples 2-4 do not have porous carbon materials with micro-nano structures (PC7~ PC9 in Table 1). In comparison, the porous carbon materials prepared in Examples 1-5 have porous carbon with rich micro-nano structures (PC1~PC5 in Table 1). The volume of micro-nano pores accounts for a large proportion of the pores under the precursor with a large total pore volume. At the same time, the specific surface area is also relatively large due to the rich pore structure. Among the porous carbons with micro-nano structures, the micro-nano porous carbon with a through-pore structure (PC1 in Table 1) has a larger total pore volume and specific surface area than the micro-nano porous carbon without through-pores (PC6 in Table 1).

[0057] The porous carbon raw material rich in micro-nano through-hole structure prepared in Example 1 and the silicon-carbon composite material obtained by vapor deposition of silicon were examined by scanning electron microscopy (SEM). Figure 1-2 As shown, Figure 1 The morphology of the porous carbon raw material rich in micro-nano through-pore structure. Figure 2 This is the morphology of the silicon-carbon composite material obtained after vapor deposition of silicon on a porous carbon substrate rich in micro-nano pore structure. Figure 3 This is a SEM photo of the cross section of the gas phase silicon-carbon composite material particles. Figure 4 is the C element distribution diagram of the cross section of the gas phase silicon-carbon composite material particles, Figure 5 This is the Si element distribution diagram of the cross section of the gas phase silicon-carbon composite material particles.

[0058] 2. Performance test of button electrode The above assembled batteries were subjected to an open circuit voltage test, and batteries with an open circuit voltage above 2.5V were selected for 0.1C first charge and discharge efficiency and reversible capacity tests; the electrical performance comparison of several batteries is shown in Table 2.

[0059] Table 2: Electrical properties of button cells

[0060] In the application of lithium-ion batteries, silicon-based negative electrode materials consume more irreversible lithium and relatively less reversible lithium due to large volume changes, silicon material particle pulverization and repeated growth of SEI film on the surface; in the performance of lithium batteries, this is directly reflected in the high lithium insertion capacity and the relatively low reversible lithium removal capacity, resulting in low initial charge and discharge efficiency; as can be seen from the above table, the porous carbon-filled nanosilicon structure based on micro-nano through-hole structure constructed in the present invention has abundant micro-nano pores that provide an elastic carbon skeleton for the expansion and contraction of nanosilicon during lithium insertion and extraction, thereby preventing the breakage of silicon particles; at the same time, the inner wall of the porous carbon micro-nano pores is tightly combined with the nanosilicon particles, which, on the one hand, increases the electronic conductivity of the silicon particles and the carbon skeleton, i.e., the entire composite particle; on the other hand, the inner wall of the carbon pore tightly wraps the silicon particles, reducing the direct contact reaction between the electrolyte and the nanosilicon, i.e., reducing the loss of reversible lithium caused by the repeated formation of SEI film on the surface of the silicon particles. Compared with the gas-phase silicon-carbon composite materials without a porous carbon skeleton with a micro-nano pore structure (such as SPC7, SPC8 and SPC9 in the table) and the gas-phase silicon-carbon composite materials with a porous carbon skeleton with micro-nano pores but non-through-pore structure (such as SPC6 in the table), the electrical properties of the gas-phase silicon-carbon composite materials with this structure (such as SPC1~SPC5 in the table) are greatly improved; the gas-phase silicon-carbon composite materials based on porous carbon rich in micro-nano through-pore structure finally prepared by the present invention have a market-competitive electrical performance level in the application field of lithium-ion battery negative electrodes.

[0061] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon material rich in micro-nano through pores, characterized in that: The following steps are involved: S1, mixing the foaming agent and the carbon source uniformly and performing isostatic pressing to obtain an isostatic pressing block; the isostatic pressing pressure is 50-300 MPa, and the processing time is 60-120 min; S2, crushing the isostatically pressed blocks obtained in step S1 to obtain crushed coarse particles; S3, performing vacuum sintering treatment on the crushed coarse particles in step S2 under the protection of inert gas to obtain primary particles; the sintering temperature of the vacuum sintering is 600-900°C, the vacuum degree is maintained at -(1.0±0.5)Kpa, and the temperature is kept for 60-120min; S4, crushing the original particles in step S3 to obtain a porous carbon material rich in micro-nano through pores.

2. The method for preparing a porous carbon material rich in micro-nano through pores according to claim 1, characterized in that: The foaming agent is selected from one or more of sodium bicarbonate, sodium carbonate, azodicarbonamide or carbon black; and the particle size D50 of the foaming agent is 1-10 μm.

3. The method for preparing a porous carbon material rich in micro-nano through pores according to claim 1, characterized in that: The carbon source is selected from one or more of asphalt, resin or organic polymer, and the particle size D50 of the carbon source is 1-30 μm.

4. The method for preparing a porous carbon material rich in micro-nano through pores according to claim 1, characterized in that: In step S1, the mass ratio of the foaming agent to the carbon source is (0.1-0.5):

100.

5. The method for preparing a porous carbon material rich in micro-nano through pores according to claim 1, characterized in that: In step S2, the size of the crushed coarse particles is 3-10 mm.

6. The method for preparing a porous carbon material rich in micro-nano through pores according to claim 1, characterized in that: In step S3, the heating rate during vacuum sintering is 0.5-5°C / min.

7. The method for preparing a porous carbon material rich in micro-nano through pores according to claim 1, characterized in that: The prepared porous carbon material rich in micro-nano pores has a pore size of 0.5~10.0nm; the pore volume accounts for 60~90%.

8. Use of the porous carbon material rich in micro-nano through pores prepared by the preparation method according to any one of claims 1 to 7 in silicon-carbon composite materials or in lithium-ion batteries.

9. A gas phase silicon-carbon composite material, characterized in that: The gas phase silicon-carbon composite material is obtained by subjecting a porous carbon material rich in micro-nano through pores prepared by the preparation method according to any one of claims 1 to 7 to silane chemical vapor deposition.

10. The gas phase silicon-carbon composite material according to claim 9, characterized in that: The temperature of the silane chemical vapor deposition is (600±100)°C, the flow ratio of the introduced silane gas to the protective gas is (0.5~1):10, and the mass percentage of the vapor-deposited silicon accounts for 40%~60% of the total mass.

Citation Information

Patent Citations

  • Preparation method of multilevel porous carbon with ultrahigh specific surface area

    CN104118861A

  • Silicon-carbon composite material based on three-dimensional network carbon-silicon structure as well as preparation method and application of silicon-carbon composite material

    CN116417602A

  • Carbon foam, systems and methods for forming the same

    US20210371284A1

  • Carbon material and process for production thereof

    US5045298A

  • Silicon-carbon composite material and negative electrode sheet containing same

    WO2024011405A1